Identification of epidemiological models: the case study of Yemen cholera outbreak. Issue 10 (3rd July 2022) - Carfora, Maria Francesca; Torcicollo, Isabella
ABSTRACT: A full ODE model for the transmission of cholera is investigated, including both direct and indirect transmission and a nonlinear growth for pathogens. The direct problem is preliminarily studied and characterized in terms of reproduction number, endemic and disease free equilibria. The inverse problem is then discussed in view of parameter estimation and model identification via a Least Squares Approximation approach. The procedure is applied to real data coming from the recent Yemen cholera outbreak of 2017–2018.